Spectrum of Bacterial Infection and Antibiotic Susceptibility Profile among Clinical Samples of Febrile Pediatric Cancer Patients under Chemotherapy - Abbas Hadi, Dalal; Abd Al-Ridha Al-Abdullah , Amani; Mahmood Salih, Hussam (International Journal of Psychosocial Rehabilitation, 2020)
Bacterial infection is one of the most frequent complications in malignant patients. Among them, those caused by multidrug-resistant (MDR) bacteria that increase mortality and morbidity mainly because of limited therapeutic options. The study material comprised 155 febrile episodes occurring in 101 children aged less than 18 years with various malignancies from May 2018 to April 2019 at Basrah Children’s Specialty Hospital. All the episodes were worked up in detail, including physical examination, history, and relevant investigations. Bacterial isolated from different sites were identified to the species level and tested for their susceptibility to a variety of antimicrobial agents A total of 61 bacteria were cultured in 155 febrile episodes. Gram-negative bacteria were more prevalent (53 [86.9%]) as a cause of infection in febrile pediatric cancer patients at our institution. Escherichia coli showed the highest isolation rate, 64.1% (34/53), followed by Klebsiella pneumoniae, 13.2% (7/53), and Proteus mirabilis, 11.3% (6/53). The rate of MDR in Gram-negative isolates was 90.5% (48/53). Gram-positive consists of 8 (13.1%) with a prevalence of Staph aureus of 37.5% (3/8) and a rate of MDR of 75% (6/8). The antibiotic susceptibility results showed meropenem, imipenem, and amikacin to be the most effective antibiotics for Gram-negative bacteria. Overall, urinary tract infections were the most common sites of infection (23.2%). The results of the analysis of the sequencing of 16SrDNA of selected 43 isolates showed 100% compatibility at the genus and species level with the results of VITEK 2. Ten isolates were registered as a new strain in Gene Bank. Gram-negative bacteria with high MDR were the more prevalent cause of infection in febrile pediatric cancer patients. Escherichia coli is the most common pathogen. The changing pattern of infectious agents in cancer patients with significant distribution of MDR suggests the need for further studies to give physicians a more recent view of bacterial isolates and antibiotic resistance patterns for appropriate therapeutic approaches.